2015
DOI: 10.1186/s12885-015-1143-y
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol of REGOSARC trial: activity and safety of regorafenib in advanced soft tissue sarcoma: a multinational, randomized, placebo-controlled, phase II trial

Abstract: BackgroundAngiogenesis, among other signaling pathways, plays a key-role in sarcoma biology. Regorafenib (RE) has recently been shown to be effective in imatinib and sunitinib-refractory GIST in a phase III trial.Methods/designWe are conducting an international trial (France, Austria and Germany) consisting in 4 parallel double-blind placebo-controlled randomized (1/1) phase II trials to assess the activity and safety of RE in doxorubicin-refractory STS (ClinicalTrials.gov: NCT01900743). Each phase II trial is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Generally, anti-angiogenesis TKIs therapy with pazopanib has been a hallmark for all non-adipocytic soft tissue sarcoma after phase II and III trial verification, with median PFS 4.6 months (3.7–4.8 m; 95% CI) and best overall objective response rate of 6% (14/246) [ 14 , 29 ]. Thomas et al [ 30 ] reported that regorafenib, which is an inhibitor of VEGFR-1, − 2 and − 3 and tumor cell signaling kinases (RET, KIT, PDGFR, and Raf), yielded median PFS of 4.6 months in advanced sarcoma patients, which was almost the same as with pazopanib. Recently, the US Food and Drug Administration approved olaratumab [ 31 ], a human antiplatelet-derived growth factor receptor α monoclonal antibody, together with doxorubicin as first-line therapy for unresectable or metastatic soft tissue sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, anti-angiogenesis TKIs therapy with pazopanib has been a hallmark for all non-adipocytic soft tissue sarcoma after phase II and III trial verification, with median PFS 4.6 months (3.7–4.8 m; 95% CI) and best overall objective response rate of 6% (14/246) [ 14 , 29 ]. Thomas et al [ 30 ] reported that regorafenib, which is an inhibitor of VEGFR-1, − 2 and − 3 and tumor cell signaling kinases (RET, KIT, PDGFR, and Raf), yielded median PFS of 4.6 months in advanced sarcoma patients, which was almost the same as with pazopanib. Recently, the US Food and Drug Administration approved olaratumab [ 31 ], a human antiplatelet-derived growth factor receptor α monoclonal antibody, together with doxorubicin as first-line therapy for unresectable or metastatic soft tissue sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Regorafenib is an orally administered small molecular multikinase inhibitor that targets tumor cells, vasculature, and tumor microenvironment (8,28). To date, preclinical studies with orthotopic colon cancer xenografts have revealed that regorafenib reduced tumor angiogenesis and inhibited tumor growth (20).…”
Section: Discussionmentioning
confidence: 99%
“…Regorafenib is another multitargeted TKI, with activity against angiogenic, stromal (VEGFR1–3, TIE2, FGFR1, and PDGFR-β), oncogenic (KIT and RET), and intracellular signaling (RAF1 and B-RAF) kinases among others, currently in Phase II trial (REGOSARC) for STS83 after showing activity in both colorectal cancer and GIST in Phase III trials 84,85. Preliminary results from REGOSARC demonstrated improved PFS and OS in patients with leiomyosarcoma and improved PFS in those with other sarcomas 86.…”
Section: Tkismentioning
confidence: 99%